AFM-IR: combining atomic force microscopy and infrared spectroscopy for nanoscale chemical characterization - Dazzi, Alexandre; Prater, Craig B; Hu, Qichi; Chase, D Bruce; Rabolt, John F; Marcott, Curtis (Applied spectroscopy, 2012)
Polymer and life science applications of a technique that combines atomic force microscopy (AFM) and infrared (IR) spectroscopy to obtain nanoscale IR spectra and images are reviewed. The AFM-IR spectra generated from this technique contain the same information with respect to molecular structure as conventional IR spectroscopy measurements, allowing significant leverage of existing expertise in IR spectroscopy. The AFM-IR technique can be used to acquire IR absorption spectra and absorption images with spatial resolution on the 50 to 100 nm scale, versus the scale of many micrometers or more for conventional IR spectroscopy. In the life sciences, experiments have demonstrated the capacity to perform chemical spectroscopy at the sub-cellular level. Specifically, the AFM-IR technique provides a label-free method for mapping IR-absorbing species in biological materials. On the polymer side, AFM-IR was used to map the IR absorption properties of polymer blends, multilayer films, thin films for active devices such as organic photovoltaics, microdomains in a semicrystalline polyhydroxyalkanoate copolymer, as well as model pharmaceutical blend systems. The ability to obtain spatially resolved IR spectra as well as high-resolution chemical images collected at specific IR wavenumbers was demonstrated. Complementary measurements mapping variations in sample stiffness were also obtained by tracking changes in the cantilever contact resonance frequency. Finally, it was shown that by taking advantage of the ability to arbitrarily control the polarization direction of the IR excitation laser, it is possible to obtain important information regarding molecular orientation in electrospun nanofibers.